Educational technology as a key enabler for achieving the Sustainable Development Goal 4 - CHI, Younsuh (KDI School, 2018)
In 2016, the world has embarked on a new journey for sustainable development, simultaneously entering the era of the 4th Industrial Revolution that accompanies huge advancement of technologies. Now that human beings are facing with daunting challenges of sustainability, the newly upcoming era is promising for far more opportunities of innovation than never before. Technology is deemed as what will be a driving force for sustainable development, and its benefits are expected to contribute to the achievement of post-2015 education goal, SDG 4, as well. In this sense, this paper first delves into the SDG 4, the Education 2030 Agenda, focusing on the main obstacles in its achievement- i) financing and ii) low quality of education. Then by looking into the overall concept of educational technology, it further explores how advancement of technologies such as Artificial Intelligence (AI), Virtual Reality (VR), Augmented Reality (AR), and Learning Analytics, can contribute to overcome such challenges by enabling various effective learning methods- Blended Learning (Flipped Learning), Massive Open Online Courses (MOOCs), Adaptive Learning, and G-Learning and Gamification. Case studies have already shown the benefits of educational technology to reduce the cost of education by allowing for the teachers to cover larger number of students at one time, as they are no longer restrained at one location thanks to the internet environment, and by letting schools to lower the tuition while saving additional cost on maintenance of the school facilities. In the meantime, quality of education can be enhanced as customized learning becomes available for every single student. Students can enjoy learning as entertaining factors are reinforced by VR/AR and gamification, and develop themselves by complementing what they are lack of, following the guidance of AI and Learning Analytics. Indeed, experts analyze that BAU (Business as Usual) approach, to stick to the conventional way of educational development of simply increasing supplies of teachers and classrooms, will no longer a solution for sustainable educational development. Despite the potential benefits of technologies, however, still only a half of the world population is online, without being prepared at all for further development and aid to education is not reflecting such current circumstantial changes. This paper argues that, thus, digital equity and digital literacy should be redressed while enhancing teacher training, and reconsideration on the priorities of aid to education needs to be preceded for educational technology to function as a true enabler for the achievement of SDG4.
Thesis(Master) --KDI School:Master of Development Policy,2018